2017
DOI: 10.5539/gjhs.v10n1p140
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parental Smoking on the Severity of Asthma in Children: A Cross-Sectional Study

Abstract: Background: Several environmental factors trigger attacks of asthma by immunological and non-immunological mechanisms. Among these factors are cited the passive or second hand smoking (SHS) which has a deleterious effect on the prognosis of childhood asthma and induces a resistance to treatment by corticosteroids. The aim of the present study was to identify parents of children with asthma who are smokers and to explore the possible negative impact of SHS exposure on the disease of asthmatic children. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Again this may be due to a low percentage of smokers among our population. A study we previously conducted to explore the effect of parental smoking on asthma exacerbation of their children showed that only 28% of parents were smokers [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Again this may be due to a low percentage of smokers among our population. A study we previously conducted to explore the effect of parental smoking on asthma exacerbation of their children showed that only 28% of parents were smokers [20] .…”
Section: Discussionmentioning
confidence: 99%